Postmortem debugging in dynamic environments. - Pacheco, David (Communications of the ACM, 2011)
The article discusses postmortem debugging in environments where dynamic languages such as Java, Python, and JavaScript were used. The article examines in situ debugging, which the author argues can only be used with reproducible problems, and examines constraints for postmortem debugging facilities as well as debugging in native environments. The author presents a postmortem debugging facility for Node.js production deployments from cloud computing software company Joyent, examining dumps, serializing circular objects, and the implementation of the program.